Evaluating the Pharmacological Efficacy of Triazole Derivatives: Molecular Docking and Anticancer Studies - Swati Udugade (International Journal of Medical Toxicology and Legal Medicine, 2024)
Triazole derivatives are promising candidates in the field of medicinal chemistry due to their diverse biological activities. This study aims to evaluate the pharmacological efficacy of triazole derivatives through molecular docking and anticancer studies. We utilized computational molecular docking to predict the binding affinity of various triazole derivatives to a selected cancer-related target protein. Introduction: Triazole derivatives are noted for their diverse biological activities, including significant anticancer properties. This study investigates the pharmacological efficacy of triazole derivatives using molecular docking and in vitro anticancer assays. Results: Molecular docking revealed strong binding affinities for several triazole derivatives, with binding energies between -8.5 to -10.2 kcal/mol. In vitro assays demonstrated significant cytotoxic effects, particularly for compounds T1, T3, and T5, with IC50 values of 15.2 µM, 10.5 µM, and 8.7 µM, respectively. Compound T5 induced cell cycle arrest at the G2/M phase and apoptosis in HeLa cells, confirmed by upregulation of Bax and caspase-3 and downregulation of Bcl-2. Conclusion: Triazole derivatives show promise as anticancer agents, evidenced by their high binding affinity to EGFR and potent cytotoxicity in cancer cell lines. These findings warrant further in vivo studies and structural optimization to enhance their therapeutic potential.